Analisis Semiotik Iklan Top Coffee Versi Iwan Fals Pada Media Televisi - Robertus Fajar Wicaksana (TUTURRUPA, 2018)
This research is based on the construction of signs which often used in advertising to conveymessage. Therefore, this research is conducted to see how the construction of signsrepresenting myth of lifestyle in Top Coffee advertising Iwan Fals version “Inspiration”. Thisresearch uses Roland Barthes’ semiotics theory. The method used in this research isBarthes’ semiotics with denotative, connotative, and myth as the devices. The approachused in this study by using qualitative, subjects wereAdvertisement Top Coffee Iwan Fals Advertising on TV. While the object of this research isthe message on the Top Coffee Advertising Iwan Fals Version. To get Top Coffee VersionIwan Fals Advertising, researchers downloading files from the internet media. Theadvertising is then used to analyze the research material. In denotative level, ads Top Coffeeversion Iwan Fals "Inspiration" only show the same character with Iwan Fals. However, theconnotative, this advertising shows a new style of coffee that their Blending Arabica andRobusta coffee into one. This ad represents the myths of the culture and people'sconfidence in Indonesia.Based on these findings, it will be better if the effect of this ad to audiences analyzed in thefuture research.